2003
DOI: 10.1177/1049732303013005002
|View full text |Cite
|
Sign up to set email alerts
|

Intrusion: The Central Problem for Family Health Promotion among Children and Single Mothers after Leaving an Abusive Partner

Abstract: Like other single-parent families, those consisting of mothers and their children who leave abusive partners/fathers are broadly viewed a deficient, high-risk structures in which children are susceptible to multiple problems. The mechanisms of strength and vulnerability in these families are poorly understood, and, consequently, their health promotion processes remain virtually unexplored. In a feminist grounded theory study of health promotion processes of single-parent families after leaving abusive partners… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
134
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(141 citation statements)
references
References 32 publications
6
134
0
Order By: Relevance
“…The results of this study increase our understanding of battered women's complex living reality, as reported by Wuest, Ford-Gilboe, Merritt-Gray and Berman, (2003). The women remarked that before the violent events, they had advised others to leave such a relationship immediately after the first sign, and they themselves had intended to do so in case of abuse.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The results of this study increase our understanding of battered women's complex living reality, as reported by Wuest, Ford-Gilboe, Merritt-Gray and Berman, (2003). The women remarked that before the violent events, they had advised others to leave such a relationship immediately after the first sign, and they themselves had intended to do so in case of abuse.…”
Section: Discussionmentioning
confidence: 71%
“…Some of the women reported that they felt insulted by health and social workers who offered haphazard services (Corbally, 2001;Wuest et al, 2003). The systems provide services where the patients/clients experience a lack of planning and knowledge.…”
Section: Discussionmentioning
confidence: 97%
“…Intrusion is also the key problem for a family's health promotion after leaving an abusive partner. Ex-partners often control the women through the children many years after separation (Wuest et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…A grounded theory study conducted by Wuest et al [58] shines light on the factors producing stress and interference in the lives of mothers and children who have left abusive relationships. They identified intrusion as the central problem for these families which interferes with the ability of victims of IPV to maintain a consistent and harmonizing family life conducive for growth and development.…”
Section: Theories Of Intimate Partner Violencementioning
confidence: 99%
“…Women with alcohol dependence, especially women with children and women who are seeking help for IPV, are often cautious of offers of social support [2,197]. This was documented in the research by Wuest et al [58] in their grounded theory study focused on intrusion. Women who are also financially dependent on social agencies may experience increased fear and negative perceptions of "help" provided by such agencies.…”
Section: Social Dimensions Of the Relationships Among Ipv Ptsd And Amentioning
confidence: 99%